KONSENTRASI MERKURI DALAM KOLAM LIMBAH PENCUCIAN LOGAM - Irawati Mei Widiastuti; Asus Maizar Suryanto Hertika; Muhammad Musa; Diana Arfiati (Fakultas Pertanian Universitas Yudharta Pasuruan, 2018)
Mercury is used as a gold binder and released into the aquatic environment that causes pollution. The concentration of mercury in gold washing wastes must be minimized so that it is not harmful to the waters. One way is to precipitate waste. This study aims to detect mercury concentrations and water quality in each reservoir pool before waste is discharged into the water. The waste pool is six pools (P1, P2, P3, P4, P5, P6) with one pool of clean water (P0). Mercury was detected using Atomic Absorption Spectrophotometry (AAS), the water quality measured was temperature, pH, and color of wastewater. The research data were analyzed descriptively. The concentration of mercury in all settling ponds was between 0.021 ± 0.002 mg / L to 0.051 ± 0.005 mg / L). The decrease in the average mercury concentration from pond P1 to P6 is 16.7%. The concentration of mercury has exceeded the maximum allowed for mercury in water. The temperature in each pond has decreased from pond P1 to P6, but pH has increased.